2021
DOI: 10.1111/1742-6723.13869
|View full text |Cite
|
Sign up to set email alerts
|

Redback spider bites in children in South Australia: A 10‐year review of antivenom effectiveness

Abstract: Objective: To describe the South Australian paediatric redback spider bite experience and to examine the hypothesis that redback antivenom (RBAV) treatment in children is clinically effective. Methods: Retrospective chart review of all children under 18 years of age presenting to the EDs of the three major paediatric or mixed hospitals in Adelaide, South Australia, with a discharge diagnosis of redback spider envenomation between 1 January 2010 and 31 March 2020. The main outcome measures include: patient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Response to Re: Redback spider bites in children in South Australia: A 10-year review of antivenom effectiveness Dear Editor, We thank Downes et al 1 for their comments regarding our paper. 2 We agree with their concern that the findings of our simple retrospective study have provided such contradictory results in comparison to the two prospective predominantly adultbased redback antivenom evaluation (RAVE) clinical trials. 3,4 We offer 'no plausible science' to explain these differences, as we recognise and have documented the limitations of our retrospective study and only suggest further prospective clinical trials in children to investigate this issue.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Response to Re: Redback spider bites in children in South Australia: A 10-year review of antivenom effectiveness Dear Editor, We thank Downes et al 1 for their comments regarding our paper. 2 We agree with their concern that the findings of our simple retrospective study have provided such contradictory results in comparison to the two prospective predominantly adultbased redback antivenom evaluation (RAVE) clinical trials. 3,4 We offer 'no plausible science' to explain these differences, as we recognise and have documented the limitations of our retrospective study and only suggest further prospective clinical trials in children to investigate this issue.…”
supporting
confidence: 83%
“…Previous research has shown that, in an unselected cohort of patients and in patients with chronic obstructive airways disease, venous values of pH are clinically interchangeable with arterial values while agreement of bicarbonate and lactate are close but less precise. 1,2 Agreement of pCO 2 is not clinically acceptable; however, it has been shown to be a good screening test for significant hypercapnia. 1,2 There is a gap in the literature regarding arteriovenous (AV) blood gas agreement in patients with severe pneumonia.…”
Section: Arteriovenous Blood Gas Agreement For Intensive Care Unit Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…
Dear Editor, We read with concern the study by Cocks et al 1 which aims to evaluate the effectiveness of redback spider antivenom (RBSAV) using a retrospective, single arm methodology. This methodology is questionable in the context of existing clinical trials, which have demonstrated RBSAV to be no better than standard analgesia alone.
…”
mentioning
confidence: 99%
“…However, ED length of stay data are not provided, which combined with a lack of follow up, make any meaningful interpretation of this difficult. 1 Pain is a significant and persistent problem in latrodectism potentially lasting up to 48 h, hence both RAVE and RAVE II randomised controlled trials reporting analgesic effect up to 24 h postadministration. 2,3 Cocks et al report 56 of 61 (92%) patients having a good response to RBSAV.…”
mentioning
confidence: 99%